"That's Not Real India": Responses to Women's Portrayals in Indian Soap Operas. (July 2016) - Somani, Indira S.; Doshi, Marissa J.
This study examined the portrayal of women on Indian soap operas through content analysis. Quotes from in-depth interviews of 100 Asian Indians (50 couples) from five major metropolitan areas, NY, DC, SF, Chicago, and Houston, who watch Indian television (imported from India) via the satellite dish or cable, were used in this study. Researchers uncovered specific themes, such as Portrayal of women, Heterosexual Romance and Intimacy, and Joint Family, and analyzed these themes against the theoretical framework of cultural proximity. The authors explained that the role of Indian women being created in Indian serials did not reflect the image of Indian women the participants remembered when they migrated to the United States in the 1960s. The image of Indian women that was being portrayed was that of a "vamp" or someone manipulative and not family-oriented. Therefore, the cultural proximity of the Indian soap operas was disrupted by the negative portrayal of Indian women to a particular generation of Indian immigrants in the United States. The participants appreciated the image of a modern Indian woman, as long as she still maintained traditional values. Further, these portrayals reminded these participants that they were cultural outsiders in modern India.